Toward A New Model For Firm Internationalization: Conservative, Predictable, and Pacemaker Companies and Markets. (11th July 2018) - Paul, Justin; Sánchez‐Morcilio, Rosarito
Abstract: Through this article we develop a new model for the internationalization of firms, called the Conservative, Predictable and Pacemaker (CPP) model, for extending research in the domain of international business. The main purpose is to provide a new typology that can be used as a theoretical lens for future research and to motivate researchers to think beyond the established models, which are repeatedly used in many studies. This article is based on primary data collected from firms in the information technology sector in Puerto Rico. The CPP model may be useful for industry analysis and research dealing with the growth and internationalization of firms across industries and countries. © 2018 ASAC. Published by John Wiley & Sons, Ltd. Résumé: Dans cet article, nous élaborons un nouveau modèle pour l'internationalisation des entreprises appelé le modèle 'Conservative, Predictable, and Pacemaker' (modèle CPP), dans le souci de contribuer à la recherche en commerce international. L'objectif principal est de fournir une nouvelle typologie capable de servir de grille théorique dans les recherches futures et d'encourager les chercheurs à penser au‐delà des modèles établis qu'on retrouve dans de nombreuses études. L'article est basé sur des données primaires recueillies auprès d'entreprises du secteur des technologies de l'information à Porto Rico. Le modèle CPP peut être utile pour l'analyse de l'industrie et pour la recherche sur la croissance et l'internationalisation des entreprises dans toutes les industries et dans tous les pays. © 2018 ASAC. Published by John Wiley & Sons, Ltd.